Complex orebodies and future global metal supply: An introduction. (August 2022) - Lèbre, Éléonore; Owen, John R.; Kemp, Deanna; Valenta, Rick K.
Abstract: This special issue aims to create a space for rethinking current approaches to "complex orebodies". Our introductory paper surveys recent developments in the field and identifies a range of challenges that are affecting our collective ability to engage the complex systems associated with future global metal supply. Interdisciplinary mining research remains in its infancy, with single-discipline, technical studies continuing to dominate. Social and environmental factors that lie "beyond the fence" are too often over-simplified and overlooked in resource characterisation and extractive industries. In this special issue, we profile developments in the field and engage the challenges of working in inter-disciplinary, boundary-spanning research in mining. Our paper introduces the special issue, and invites contributing authors to critically engage the conditions and prospects that lie ahead. Highlights: This special issue rethinks current approaches to "complex orebodies". Current approaches provide overlapping risk concepts e.g. supply risks or ESG risks. Recurring challenges affect the comprehension of complex mineral resource systems. Authors are invited to de-centre conventional knowledge boundaries. And to challenge established norms around risk definition and risk mitigation.